Relationship Between Human Development Index And Poverty Percentage In East Java In 2023 - Saputri, Nuke Aulia; Deffinika, Ifan (UNIVERSITAS PAKUAN, 2025)
This research was used to analyze, understand and identify the relationship between the human development index and the percentage of poverty in East Java in 2023, the period of economic recovery after the Covid-19 pandemic. Poverty is a complex problem related to population, economics, social and culture. East Java is the third poorest province on the island of Java, with a poverty rate of 10.35% as of March 2023. Sampang City is the city with the highest poverty rate, namely 21.76%. The simple correlation method is used to analyze the relationship between two variables and also measure the strength and direction of influence of the variables used so that it can be identified how big the relationship between variables is statistically. The variables used are the human development index value for one year (2023) and the poverty percentage variable in 2023. The results of decision making after processing the data, it can be concluded that the HDI results have a relationship with the poverty percentage of East Java in 2023 with a correlation value amounting to 0.810 which is included in the strong correlation category so that the research hypothesis can be accepted. The correlation in the research has a negative direction. Negative correlation means that an increase in the HDI variable is accompanied by a decrease in the percentage of poverty, and vice versa.